2019
DOI: 10.3390/cancers12010064
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing of Collecting Duct Renal Cell Carcinoma Suggests an Interaction between miRNA and Target Genes and a Predominance of Deregulated Solute Carrier Genes

Abstract: Collecting duct carcinoma (CDC) is a rare renal cell carcinoma subtype with a very poor prognosis. There have been only a few studies on gene expression analysis in CDCs. We compared the gene expression profiles of two CDC cases with those of eight normal tissues of renal cell carcinoma patients. At a threshold of |log2fold-change| ≥1, 3349 genes were upregulated and 1947 genes were downregulated in CDCs compared to the normal samples. Pathway analysis of the deregulated genes revealed that cancer pathways and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…Thus, our knowledge regarding potential ccRCC biomarkers for guiding intervention and surveillance has recently been dramatically expanded. Recent article by Wach et al reported the RNA sequencing of collecting duct carcinoma, a rare renal cell carcinoma subtype with a very poor prognosis and solute carrier (SLC) gene family (SLC3A1, SLC9A3, SLC26A7, and SLC47A1) was included in the most downregulated genes [24]. According to this study trend, our newly identified biomarkers may further aid in unraveling the evolutionary trajectories of ccRCC tumor growth.…”
Section: Discussionmentioning
confidence: 65%
“…Thus, our knowledge regarding potential ccRCC biomarkers for guiding intervention and surveillance has recently been dramatically expanded. Recent article by Wach et al reported the RNA sequencing of collecting duct carcinoma, a rare renal cell carcinoma subtype with a very poor prognosis and solute carrier (SLC) gene family (SLC3A1, SLC9A3, SLC26A7, and SLC47A1) was included in the most downregulated genes [24]. According to this study trend, our newly identified biomarkers may further aid in unraveling the evolutionary trajectories of ccRCC tumor growth.…”
Section: Discussionmentioning
confidence: 65%
“…From the perspective of posttranscriptional modification, accumulating evidence demonstrates that SLC7A11 mRNA is derepressed by decreased miR-26b in human breast cancer and miR-375 in oral squamous cell carcinoma (34)(35)(36). And bioinformatic analysis predicted that SLC7A11 is targeted by different miRNAs, including has-mir-373 and has-mir-372 (37), miR-374b-5p and miR-26b-5p (38), and miRNA-126-3p/5p (39), but whether and how these miRNAs regulate SLC7A11 are not clear. In the present study, we predicted the candidate target genes for miR-27a-3p using TargetSan, miRanda, microT, PITA, miRmap, and PicTar platform.…”
Section: Mir-27a-3p Regulates Erastin Induced Ferroptosis In Nsclc Cellsmentioning
confidence: 99%
“…Additional transcriptomic data of CDC and normal samples were downloaded from the Gene Expression Omnibus (GEO) repository (raw RNA-Seq counts of GSE89122 [12] and raw microarray data of GSE11151 [17]). A third dataset, hereafter named Wach, was built from the raw RNA-Seq counts included in Table S7 of the corresponding publication [14].…”
Section: Retrieval Of Public Gene Expression Datamentioning
confidence: 99%
“…Transcriptomic profiling through RNA sequencing (RNA-Seq), performed on seven CDC and four matched normal kidney samples, highlighted the dysregulation of several solute carrier family genes including tumor overexpression of SLC7A11, a cisplatin-resistance marker [12]. An independent study on two CDC and eight normal kidney samples reported an overexpression of cancer-related and cell cycle pathways in CDC, in addition to the modulation of SLC genes [14]. Another RNA-Seq study of 11 CDC and nine upper-tract urothelial carcinoma (UTUC) samples compared with additional renal cancer cell (RCC) histologies from the cancer genome atlas (TCGA) showed that CDC tumors clustered separately from other tumor types [15].…”
Section: Introductionmentioning
confidence: 99%